ANALISIS TERHADAP APLIKASI AKAD MURABAHAH DI BANK SYARIAH - Nofinawati, Nofinawati (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2016)
Transactions of murabahah are also the biggest transactions in Indonesia sharia‟s banking, as we know in International Islamic Banking. Based on sharia‟s banking statistic at december 2014, published by Otoritas Jasa Keuangan (OJK), financing portfolio of murabahah is 117,371 billion rupiahs. This is the highest number compare to the others. Akad mudharabah, musyarakah, ijarah, qardh, and istishna‟ each are 14,354 billion, 49,837 billion, 11,464 billion, 5,965 billion and 0,633 billion rupiahs. Nowadays, there are many costumer that still unwilling to apply akad murabahah in sharia bank. The result of this study shows that the application of murabahah in Indonesia sharia banks is not against Islamic sharia law.